Literacy skills, mathematical skills and educational expectations among Finnish adolescents - Niiva, Henna (2013)
This study investigated the connection between educational expectations and skills in spelling, reading fluency and mathematics among Finnish 9th Graders. Connection between comorbidity of reading disability and mathematical disability with educational expectations was also examined. These connections were explored among boys and girls and the effects of parental education were assessed, as well. Cross tabulations and analyses of variance were used as tools for analyses. Spelling, reading fluency and mathematics were connected to educational expectations, with higher skills leading to higher expectations. The largest difference between the educational expectation groups was in mathematics. Adolescents with reading disability (RD), mathematical disability (MD), or both set their educational expectations lower than peers with good skills. Mathematics functioned as compensating factor against the effects of RD of educational expectations, but only in boys. As unresolved expectations were fairly common, the need of more information about educational and occupational options for adolescents was suggested. Attitudes of girls towards mathematics should also be targeted and encouraged. Parental education was found to influence adolescents’ secondary education choice. In addition, when parents had high education, the spelling skills of the adolescent contributed to their educational expectations, whereas in other parental education groups, spelling skills did not contribute to educational expectations. Highly educated parents may have more information considering different education options and that is why they could be more skillful in advising their children in educational choices. This contributes to the suggestion of more information for both adolescents and their parents. Further research about the effects of comorbidity on educational expectations is suggested.